(3QSGdI aj Yde GdehSjbis - (3aJM Gddg GdTQhGfjs
(3ChdgG (B:s
(3CeG HYO aEf CjgG GdeJhNi ai eSGQM GdCfXGQ eGjQhbc MdGhJg agPG Edjc ai gPg GdeLdg ef fbGhI eJhNGc hUHGHg eJMQGc ai Yde GdehSjbi s
(3BNQgG (B:s
(3agPG BNQ eG CQOJ EjQGOg ef gPg GdeLdI hGdMeO ddg s
(3CdagG ddSdWGf GdYKeGfi eMeO eQGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B55 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeO GdKGdK (B(3430) s
Keywords: (3GdehSjbi hGdZfGAs